2021
DOI: 10.1186/s12879-021-05850-0
|View full text |Cite|
|
Sign up to set email alerts
|

Comparative efficacy, safety and durability of dolutegravir relative to common core agents in treatment-naïve patients infected with HIV-1: an update on a systematic review and network meta-analysis

Abstract: Background The objective of this study was to assess the durability of response of dolutegravir (DTG) as an antiretroviral core agent by comparing its efficacy and safety with other recommended or commonly used core agents up to 96-weeks (W96). Methods A previously published systematic review was updated to identify phase 3/4 randomised controlled trials (RCTs) of core agents in treatment-naïve HIV-1 patients. Efficacy [virologic suppression (VS), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 29 publications
4
29
0
Order By: Relevance
“…Virological suppression in the dolutegravir group at 96 weeks according to the FDA snapshot algorithm (which incorporates information on treatment changes, deaths, and losses to follow-up) was similar (32 [76%] of 42 children with viral load <400 copies per mL) to that in older children in the dolutegravir group in the main ODYSSEY trial (82%) 15 and adults receiving dolutegravir (around 80-90% on first-line ART at 96 weeks and around 75% on second-line ART at 48 weeks). [6][7][8][9][10][11]13 A lower proportion of participants in the dolutegravir group had NRTI-resistant mutations after treatment failure than in the standard of care group; this finding is likely to be due to the combination of faster suppression and a lower rate of viral rebound with dolutegravir. One child in the below 14 kg cohort who experienced virological failure on second-line dolutegravir-based ART had potential low-level resistance to dolutegravir at treatment failure, with resistance also to zidovudine and lamivudine; the child achieved viral suppression again after failure without a change in ART.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Virological suppression in the dolutegravir group at 96 weeks according to the FDA snapshot algorithm (which incorporates information on treatment changes, deaths, and losses to follow-up) was similar (32 [76%] of 42 children with viral load <400 copies per mL) to that in older children in the dolutegravir group in the main ODYSSEY trial (82%) 15 and adults receiving dolutegravir (around 80-90% on first-line ART at 96 weeks and around 75% on second-line ART at 48 weeks). [6][7][8][9][10][11]13 A lower proportion of participants in the dolutegravir group had NRTI-resistant mutations after treatment failure than in the standard of care group; this finding is likely to be due to the combination of faster suppression and a lower rate of viral rebound with dolutegravir. One child in the below 14 kg cohort who experienced virological failure on second-line dolutegravir-based ART had potential low-level resistance to dolutegravir at treatment failure, with resistance also to zidovudine and lamivudine; the child achieved viral suppression again after failure without a change in ART.…”
Section: Discussionmentioning
confidence: 99%
“…4,5 Previous trials have shown that dolutegravir-based ART regimens are safe and effective at achieving high rates of virological suppression among adults living with HIV. [6][7][8][9][10] Dolutegravir-based regimens are also more durable with a lower risk of developing major drug resistance mutations compared with non-nucleoside reverse transcriptase inhibitor (NNRTI)-based ART regimens. 8,9,[11][12][13] The ODYSSEY trial aimed to compare the efficacy and safety of dolutegravir-based ART versus standard of care in children starting first-line or secondline ART.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a recent systematic review and meta-analysis, DTG was found to be the most effective treatment for patients with HIV, even in difficultto-treat individuals. [15] Moreover, in patients with a high viral load (>100 000 copies/mL), DTG was associated with a higher proportion of patients achieving viral suppression at 96 weeks compared with those on other ART regimens. [15] Rapid viral suppression is a critical public health goal to reduce HIV transmission.…”
Section: Rapid Viral Suppressionmentioning
confidence: 97%
“…15 In 2017, the generic DTG was introduced in India. All major guidelines [16][17][18][19] and network meta-analysis (NMA) [20][21][22] recommend DTG based regimens as preferred first-line ART in treatment naïve HIV patients. Also, DTG based regimens are now the standard of care in HIV treatment as per WHO guidelines.…”
Section: Introductionmentioning
confidence: 99%